He did what? The role of diagnosticity in revising implicit evaluations. [article]. - Cone, Jeremy; Ferguson, Melissa J.
Research suggests that implicit evaluations are relatively insensitive to single instances of new, countervailing information that contradicts prior learning. In 6 experiments, however, we identify the critical role of the perceived diagnosticity of that new information: counterattitudinal information that is deemed highly diagnostic of the target?s true nature leads to a complete reversal of the previous implicit evaluation. Experiments 1a and 1b establish this effect by showing that newly formed implicit evaluations are reversed minutes later with exposure to a single piece of highly diagnostic information. Experiment 2 demonstrates a valence asymmetry in participants? likelihood of exhibiting rapid reversals of newly formed positive versus negative implicit evaluations. Experiment 3 provides evidence that a target must personally responsible for the counterattitudinal behavior and not merely incidentally associated with a negative act. Experiment 4 shows that participants exhibit revision only when they judge the target?s counterattitudinal behavior as offensive and thus diagnostic of his character. Experiment 5 demonstrates the behavioral implications of newly revised implicit evaluations. These studies show that newly formed implicit evaluations can be completely overturned through deliberative considerations about a single piece of counterattitudinal information. - - (from the authors)